2020
DOI: 10.1186/s12939-020-01185-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of maternal death reviews at a rural hospital in Zambia: a mixed methods study

Abstract: Background: Maternal mortality in sub-Saharan Africa remains high despite programmatic efforts to improve maternal health. In 2007, the Zambian Ministry of Health mandated facility-based maternal death review (MDR) programs in line with World Health Organization recommendations. We assessed the impact of an MDR program at a district-level hospital in rural Zambia. Methods: We conducted a mixed methods convergent study using hospital data on maternal mortality and audit reports of 106 maternal deaths from 2007 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…While this pre-post evaluation approach without comparison group has some limitations, it has been considered justifiable for projects using best practice interventions that have been previously proven to work under similar conditions [11,31]. Finally, the community surveillance approach used for population mortality data was established to be beneficial not only for purposes of program evaluation but as a sustainable solution for capturing community mortality data, strengthening the ability of the government to carry out MPDSR reviews for all community and facility deaths, and increasing levels of community buy-in and stakeholder support, which can in turn facilitate further reductions in mortality [17,32]. While our approach cannot completely isolate the impact of this program from generalized ecological trends, there were no major partner-supported reproductive health programs taking place in Northern Province at the time of this work, which supports impact attribution for this program.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…While this pre-post evaluation approach without comparison group has some limitations, it has been considered justifiable for projects using best practice interventions that have been previously proven to work under similar conditions [11,31]. Finally, the community surveillance approach used for population mortality data was established to be beneficial not only for purposes of program evaluation but as a sustainable solution for capturing community mortality data, strengthening the ability of the government to carry out MPDSR reviews for all community and facility deaths, and increasing levels of community buy-in and stakeholder support, which can in turn facilitate further reductions in mortality [17,32]. While our approach cannot completely isolate the impact of this program from generalized ecological trends, there were no major partner-supported reproductive health programs taking place in Northern Province at the time of this work, which supports impact attribution for this program.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In 2018, it was estimated that Zambia’s maternal mortality ratio (MMR) was 282 per 100,000, and the majority of the maternal deaths were directly caused by OH [ 2 , 3 ]. A recent evaluation of maternal death reviews (MDRs) at a rural hospital in Zambia found that maternal deaths from all causes decreased over the course of five years, with the exception of deaths from postpartum hemorrhage, a key type of OH [ 4 ]. Case reviews showed that issues of accessibility, such as poor road conditions, as well as issues related to the health system, such as delayed referrals, as well as lack of stabilizing measures before referral are major contributors to this persistent problem.…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, the Zambian Ministry of Health implemented a new WHO-recommended roadmap for reproductive health including the maternal death review (MDR) system in line with World Health Organization recommendations which was able to reduce maternal mortality rates to a great extent in the country. 9 Another mention-worthy example of private-private partnership the Saving Mothers, Giving Life (SMGL) program that is target to reduce maternal mortality through a systems approach and healthcare capacity building. 4 …”
Section: Introductionmentioning
confidence: 99%
“…7,8 A large number of studies have highlighted the importance of socioeconomic factors in maternal health and healthcare service utilization related outcomes. 4,[8][9][10] Although healthcare seeking as a behavior is considered to be driven to a great extent by perceived need of care and health literacy, the critical role one's financial capacity to medical services cannot be overestimated especially in the low-income countries like Zambia where there is not universal healthcare system to safeguard the health needs of the disadvantaged communities. This growing popularity of social cash transfer programs to promote maternal health provides a strong evidence on the role of socioeconomic determinants as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation